DEVELOPMENT OF STEM-BASED THERMODYNAMICS E-MODULES INTEGRATED WITH PROBLEM SOLVING TO IMPROVE CRITICAL THINKING SKILLS AND LEARNING OUTCOMES - Parwiti, Endang; Siregar, Tiurlina; Albaiti, Albaiti (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
Abstract: This study aims to determine how to create, develop and feasibility of STEM-based thermodynamics e-modules integrated with problem solving in improving critical thinking skills and learning outcomes of class XI students of SMA YPK Bintuni. The research method is research and development (R&D) by adopting five stages of the ADDIE model (analyze, design, develop, implement and evaluate). The instruments used in the study were e-module feasibility test sheets, learning outcome tests and critical thinking ability test results for the trial use of e-modules. E-modules were analyzed empirically using the SPSS version 20 application. The developed e-modules have been validated using a Likert scale on aspects of content feasibility, language feasibility and presentation feasibility. The sampling technique was purposive sampling, with a research sample of class XI IPA SMA YPK Bintuni with a total of 20 people. The results showed that the developed STEM-based Thermodynamics e-module integrated with problem solving was very feasible to be used in learning with an average validator assessment of 90%. The Thermodynamics e-module is practical to use and effective in improving critical thinking skills and student learning outcomes, obtaining n-Gain of 0.53 in the medium category and 0.71 in the high category respectively. Keywords: E-module, Thermodynamics, critical thinking skills, problem solving, STEM. Abstrak: Penelitian ini bertujuan untuk mengetahui cara membuat, mengembangkan dan kelayakan e-modul termodinamika berbasis STEM terintegrasi problem solving dalam meningkatkan kemampuan berpikir kritis dan hasil belajar peserta didik kelas XI SMA YPK Bintuni. Metode penelitian ini adalah research and devolopment (R&D) dengan mengadopsi lima tahapan model ADDIE (analyze, design, devolopmnet, implemention dan evaluation). Instrumen yang digunakan pada penelitian adalah lembar uji kelayakan e-modul, tes hasil belajar dan tes hasil kemampuan berpikir kritis peserta didik untuk uji coba penggunaan e-modul. E-modul dianalisis secara empirik menggunakan aplikasi SPSS versi 20. E-modul yang dikembangkan telah divalidasi menggunakan skala likert pada aspek kelayakan isi, kelayakan bahasa dan kelayakan penyajian. Teknik pengambilan sampel adalah purposive sampling, dengan sampel penelitian kelas XI IPA SMA YPK Bintuni dengan jumlah 20 orang. Hasil penelitian menunjukkan bahwa e-modul Termodinamika berbasis STEM terintegrasi problem solving yang dikembangkan sangat layak untuk digunakan dalam pembelajaran dengan rata-rata penilaian validator sebesar 90%. E-modul Termodinamika tersebut praktis digunakan, dan efektif untuk meningkatkan kemampuan berpikir kritis dan hasil belajar peserta didik memperoleh n-Gain masing-masing 0,53 kategori sedang dan 0,71 kategori tinggi. Kata kunci: E-modul, Termodinamika, kemampuan berpikir kritis, problem solving, STEM